Simulation Analysis of Friction Moment Characteristic of Rolling-sliding Bearing - Liming Lu; Zhi Niu; Jinfu Lu; Fu Li (Jixie chuandong)
It is difficult to measure the friction torque of bearing parts in practice. In order to study the variation law of the friction torque of rolling-sliding bearings and the influence of the structure parameters on it， the simulation analysis of rolling-sliding bearings is carried out by using Abaqus software to guide the structural design of the new bearing. The results show that the friction torque of the rolling-sliding bearing is from small to big， then to small， finally to stable. And the starting friction torque of the rolling-sliding bearing increases with the increase of the radial clearance and decreases with the increase of the clearance between the roller and the slider， the starting friction torque between the slider and the inner ring increases with the increase of the inner arc radius of the slider， the starting friction torque between the slider and the outer ring decreases with the increase of the outer arc radius of the slider. And after stable motion， the friction torque of the rolling-sliding bearing decreases with the increase of the radial clearance and the clearance between the roller and the slider， and the friction torque between the slider and the inner ring increases with the increase of the inner arc radius of the slider， and the friction torque between the slider and the outer ring decreases with the increase of the outer arc radius of the slider.